Analisis Molecular Docking Senyawa Fitokimia Tanaman Obat Indonesia terhadap Human Rhinovirus VP1 untuk Terapi Flu Biasa - Mutiara Annisa; Deski Beri (Lembaga Yasin AlSys, 2026)
Although Indonesian traditional medicinal plants have been widely used in natural medicine, molecular docking-based studies on the potential of their bioactive compounds as antiviral agents against Rhinovirus 2R06 still need to be developed. This study aims to examine the potential of bioactive compounds from four Indonesian traditional medicinal plants, namely benzoin (Styrax benzoin), turmeric (Curcuma longa), gotu kola (Centella asiatica), and castor leaves (Ricinus communis), as antiviral candidates against Rhinovirus 2R06, one of the main causes of the common cold. This study used a quantitative in silico-based approach through the molecular docking method with MOE 2022 software. The analysis was conducted to evaluate the binding affinity and stability of bioactive compound interactions with the target protein based on S-score and RMSD values. The results showed that curcumin and demethoxycurcumin (DMC) had strong binding affinities, as indicated by highly negative S-score values and low RMSD values. Both compounds formed stable interactions with important residues, such as Leu106 and Val188, through hydrogen bonds. Thus, bioactive compounds from Indonesian traditional medicinal plants, particularly curcumin and DMC, have the potential to be developed as natural therapeutic candidates for respiratory tract infections caused by Rhinovirus 2R06. This study provides an initial basis for the development of phytochemical compound-based antiviral agents, although further experimental validation is required to support their clinical application.